أحكام الحضانة في الفقه الإسلامي وقانون الأحوال الشخصية الليبي - Isniba, Abdallah Elsharif Ahmed; Ezbeyda, Hamed Abdelsalam Mansour (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2024)
Abstract: There are childcare problems from the perspective of Sharia and the Personal Status Law. This research deals with the provisions of custody in Islamic jurisprudence compared to the Libyan Personal Status Law. The research is a normative jurisprudential and inductive approach by Comparative analysis through the study of the provisions of Islamic Sharia related to the subject of research and compared with the provisions of the Libyan Personal Status Law. The study reached several results that the Libyan Personal Status Law "Marriage and Divorce Law No. 10 of 1984", with regard to the provisions of custody is largely consistent with the provisions of custody in Islamic jurisprudence, and that custody is required based on the most compassion and mercy of the child, so the right of women to custody is ahead of men, and the right of the mother is ahead of everyone, and obligated the father of the child At his expense of housing, food, drink and custody fees, and the custodian does not prevent the guardian of the child from seeing the child, in order to preserve the growth and stability of the child emotionally and psychologically.Keywords: Custody; Islamic Law; Personal Status Law. الملخص: يدور موضوع الدراسة حول الحضانة باعتبارها من أهم الأمور التي أولتها الشريعة الإسلامية عناية خاصة. لذلك هذا البحث يتناول أحكام الحضانة في الفقه الإسلامي مقارنة بقانون الأحوال الشخصية الليبي رقم 10 لسنة 1984م. ويوضح بشكل لا لبس فيه كافة الحقوق والواجبات الشرعية والقانونية لحفظ وصيانة الأطفال، والمنهج الذي اتبعه الباحث هو المنهج الاستقرائي المقارن التحليلي من خلال دراسة أحكام الشريعة الإسلامية المتعلقة بموضوع البحث ومقارنتها بنصوص قانون الأحوال الشخصية الليبي، وتوصلت الدراسة لعدة نتائج أهمها: أن قانون الأحوال الشخصية الليبي" قانون الزواج والطلاق رقم 10 لسنة 1984م"، فيما يتعلق بأحكام الحضانة يتفق إلى حد كبير مع أحكام الحضانة في الفقه الإسلامي، وأن الحضانة تتعين بناءً على الأكثر شفقة ورحمة بالمحضون لذلك كان حق النساء في الحضانة مقدم على الرجال، وحق الأم مقدم على الجميع، وألزمت والد المحضون بنفقته من مسكن ومأكل ومشرب وأجرة حضانته، ولا تمنع الحاضنة ولي المحضون من رؤية الصغير، حفاظاً على نمو واستقرار المحضون عاطفياً ونفسياً.الكلمات المفتاحية: الحضانة؛ الفقه؛ قانون الأحوال الشخصية